Better together? Lessons on sociality from Trichodesmium - Eichner, Meri; Inomura, Keisuke; Pierella Karlusich, Juan José; Shaked, Yeala (Trends in microbiology, 2023)
The N2-fixing cyanobacterium Trichodesmium is an important player in the oceanic nitrogen and carbon cycles. Trichodesmium occurs both as single trichomes and as colonies containing hundreds of trichomes. In this review, we explore the benefits and disadvantages of colony formation, considering physical, chemical, and biological effects from nanometer to kilometer scale. Showing that all major life challenges are affected by colony formation, we claim that Trichodesmium's ecological success is tightly linked to its colonial lifestyle. Microbial interactions in the microbiome, chemical gradients within the colony, interactions with particles, and elevated mobility in the water column shape a highly dynamic microenvironment. We postulate that these dynamics are key to the resilience of Trichodesmium and other colony formers in our changing environment.
Keywords: Trichodesmium; fixace dusíku; Nitrogen Fixation; Cyanobacteria; sinice; Oceans and Seas; sociální chování; oceány a moře; Social Behavior